CYP polymorphisms and pathological conditions related to chronic exposure to organochlorine pesticides. (2017) - Docea, Anca Oana; Vassilopoulou, Loukia; Fragou, Domniki; Arsene, Andreea Letitia; Fenga, Concettina; Kovatsi, Leda; Petrakis, Dimitrios; Rakitskii, Valerii N.; Nosyrev, Alexander E.; Izotov, Boris N.; Golokhvast, Kirill S.; Zakharenko, Alexander M.; et al.
Graphical abstract: Highlights: Organochlorine compounds (OCs) are persistent organic pollutants acting as endocrine disruptors. Exposure to OCs is a risk factor for several severe pathologies. Specific CYP polymorphisms could affect the clinical impact of OCs exposure. Abstract: The association between genetic variations in the cytochrome P450 (CYP) family genes and pathological conditions related to long-term exposure to organochlorine compounds (OCs) deserves further elucidation. OCs are persistent organic pollutants with bioaccumulative and lipophilic characteristics. They can act as endocrine disruptors and perturb cellular mechanisms. Prolonged exposure to OCs has been associated with different pathological manifestations. CYP genes are responsible for transcribing enzymes essential in xenobiotic metabolism. Therefore, polymorphisms in these genetic sequences a. alter the metabolic pathways, b. induce false cellular responses, and c. may provoke pathological conditions. The main aim of this review is to define the interaction between parameters a, b and c at a mechanistic/molecular level, with references in clinical cases.